SPLUMA: The transformation of land use planning administration and governance in South Africa - Aneri Heukelman; Elizelle Juanée Cilliers (Potchefstroom Electronic Law Journal)
The physical administration of land use planning and management underwent a fundamental change upon the enactment and implementation, of the Spatial Planning and Land Use Management Act 16 of 2013 (SPLUMA), partly because section 33(1) of this Act provides that the municipality is the body of first instance for land use applications. The structural and administrative change of decision-making and record-keeping moved from a dual system of land-use administration, formerly shared by the provincial government and the local government, entirely to being the responsibility of the local government. This included the land use administration of traditional areas, mostly land owned by national government. This also implies that the historical division between urban, rural, traditional and agricultural areas, has been unified under the municipal area in terms of the wall-to-wall land use scheme and subsequent land use planning and development administration. This follows the 1996 constitutional requirement that municipal areas cover the entire country. This article considers the transformation of land use planning administration and governance in terms of land use planning and development administration.  It considers the legislative frameworks, before and after the promulgation of the Constitution of 1996, that inform land use planning and relevant to the transformation to the SPLUMA land use management system. The administrative effects that changing legislation and geographical structures have on the land use system are discussed.